Soil water use by apple trees : a thesis presented in partial fulfillment of the requirements for the Master of Agricultural Science in Soil Science at Massey University, New Zealand - Rahardjo, Pudjo (Massey University, 1989)
The study investigated the soil water use of an unirrigated tree and an irrigated apple tree in Hawke's Bay, New Zealand in the middle of the summer of 1988/1989. A rainout shelter was used to eliminate any water inputs from both irrigation and rain to the unirrigated tree. The irrigated tree received water inputs from both irrigation and rain. The soil water content was measured by neutron probing and time domain reflectometry. The heat pulse technique was used to measure the sap-flow in the apple trunks. Both leaf water pressure potential and stomatal resistance were measured by the pressure chamber and porometer respectively. A measuring cylinder was used to monitor the apple growth during the study. The results of the water use measurements were that - the neutron probing and time domain reflectometry showed the soil water use was about 77 litres (4.3 mm) per day taken from 0 - 1900 mm depth around the irrigated tree. However soil water extraction around the unirrigated tree was only 19 litres (1 mm) per day at the beginning of the study, and no water extraction was measured from the top 1900 mm later in the study. - the heat pulse technique showed that the unirrigated tree extracted slightly more soil water than the irrigated tree. The average sap-flow measured was 66 litres per day. Probably the unirrigated tree extracted much of its water from below 1900 mm depth, or from beyond the covered area. - the amount of water use by the apple trees was similar to regional evaporation estimates obtained using the Priestley - Taylor formula, when 0.66 fractional canopy cover was assumed. The water stress monitoring showed that a pressure chamber technique was a more sensitive way to monitor ress than was porometry. e leaf water pressure potential values showed a significant difference between the irrigated and the unirrigated apple tree ring the latter part of the study. The readily available soil water storage capacity from 0 to 400 depth (the most active part of the root zone) , from 0 - 1000 mm h, and from 0 to 1900 mm, was about 36 mm, 89 mm and 170 mm actively. When there was a lack of available soil water on the oil, the root system was forced to extract soil water from deep in soil profile. The comparison of apple fruit growth showed that during the last days of the study, the apples on the unirrigated tree grew more ly than those on the irrigated tree.
Keywords: Plant-water relationships; Water requirements Apples; Absorption of water by plants